Kesuksesan Sistem Informasi Rencana Kerja dan Anggaran (SIREKA) Menggunakan Model DeLone & McLean (Studi pada Universitas Brawijaya) - Ningsih, Vivi Yanuari; Hakim, Abdul; Haris Wanto, Alfi (Jurnal Ilmiah Administrasi Publik, 2019)
SIREKA is an Information System for Work and Budget Plans that is used to make and revise budget planning starting from the output, component of activities, activities and to the details of activities and using certain budget lines. This study aims to examine the Information System Success Model proposed by DeLone and McLean on the work plan and budget information system (SIREKA). The variables used in this study are system quality, information quality, service quality, usage, user satisfaction, and net benefits. Research applies the theory put forward by DeLone and McLean (2003) about the success of information systems. The results of this study show that from 9 (nine) hypotheses submitted, 6 (six) hypotheses were accepted and 3 (three) hypotheses were rejected. Thus, in general the Delone & Mclean success model is a framework that can be used as a reference to provide an evaluation of the implementation of the work plan and budget information system (SIREKA) in Universitas Brawijaya.